Defying Gravity and Conventions: Pole Dancing in Metro Manila, Philippines - Maguddayao, Adrienne Sheryl Rose L. (Review of Women's Studies, 2023)
This is an exploratory study on the demographic and motivation profiles of pole dance enthusiasts in Metro Manila, Philippines. It hopes to provide a baseline study for future academic research on pole dancing in the country. Specifically, the study aims to (1) present a brief history of pole dancing as a fitness activity in the Philippines, (2) collect the demographic profile of pole dance enthusiasts in Metro Manila, (3) examine their reasons for pole dancing, (4) expose the issues they face in relation to their pole dancing, and (5) explore how they handle these issues. A survey, participant observation, and key informant interviews were conducted to achieve these objectives. The study applies the Self-Determination Theory of Deci and Ryan, the Flow Theory of Csikszentmihalyi, and the Optimal Distinctiveness Theory of Brewer in the discussion of results.